The sedentary office: an expert statement on the growing case for change towards better health and productivity - John P. Buckley; Alan Hedge; Thomas E. Yates; Robert J. Copeland; Michael Loosemore; Mark Hamer; Gavin Bradley; David W. Dunstan (2015)
An international group of experts convened to provide guidance for employers to promote the avoidance of prolonged periods of sedentary work. The set of recommendations was developed from the totality of the current evidence, including long-term epidemiological studies and interventional studies of getting workers to stand and/or move more frequently. The evidence was ranked in quality using the four levels of the American College of Sports Medicine. The derived guidance is as follows: for those occupations which are predominantly desk based, workers should aim to initially progress towards accumulating 2 h/day of standing and light activity (light walking) during working hours, eventually progressing to a total accumulation of 4 h/day (prorated to part-time hours). To achieve this, seated-based work should be regularly broken up with standing-based work, the use of sit–stand desks, or the taking of short active standing breaks. Along with other health promotion goals (improved nutrition, reducing alcohol, smoking and stress), companies should also promote among their staff that prolonged sitting, aggregated from work and in leisure time, may significantly and independently increase the risk of cardiometabolic diseases and premature mortality. It is appreciated that these recommendations should be interpreted in relation to the evidence from which they were derived, largely observational and retrospective studies, or short-term interventional studies showing acute cardiometabolic changes. While longer term intervention studies are required, the level of consistent evidence accumulated to date, and the public health context of rising chronic diseases, suggest initial guidelines are justified. We hope these guidelines stimulate future research, and that greater precision will be possible within future iterations.